(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines how natural elements such as water, sky, and earth are conceptualized metaphorically in English and Uzbek languages. By analyzing a representative corpus of idiomatic expressions and proverbs from both linguistic and cultural perspectives, the research highlights common metaphorical patterns as well as significant divergences shaped by differing ecological environments and sociocultural contexts.